Molecular sieve SSZ-121 with high acidity, synthesis and use thereof
By introducing 1,3-bis(1-adamantyl)imidazole cation and boron path into zeolite materials, the problem of insufficient catalytic performance of existing zeolite materials is solved, and the acidic enhancement and catalytic characteristics are improved. .
Patent Information
- Application Number
- CN202380049950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-30
- Publication Date
- 2025-02-14
AI Technical Summary
The existing zeolite materials have insufficient catalytic performance in organic compound conversion reactions, and it is difficult to prepare purer single-phase materials.
The new crystalline aluminum germanium silicate molecular sieve SSZ-121 is synthesized by using 1,3-bis(1-adamantyl)imidazole cations as structural guides, combining with boron pathways, increasing its acidity.
The acidic enhancement of SSZ-121 molecular sieve was achieved, which increased its catalytic properties, and maintained a smaller boron content by replacing boron by aluminum, improving the purity and performance of the material.
Smart Images

Figure CN119451915A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 365,527, filed on May 31, 2022, the complete disclosure of which is incorporated herein by reference in its entirety. Field of the Invention
[0003] The present disclosure relates to a novel synthetic crystalline aluminogermanosilicate molecular sieve designated as SSZ-121 having increased acidity and its synthesis.
[0004] Known zeolite materials have utility as sorbents and have catalytic properties for various types of organic compound conversion reactions. Some zeolite materials are ordered porous crystalline materials with a clear crystalline structure as determined by X-ray diffraction, in which there are a large number of smaller cavities that can be interconnected by many smaller channels or holes. These cavities and holes are uniform in size in a specific zeolite material. Because the size of these holes accepts adsorbed molecules of some sizes and rejects those molecules of larger size, these materials have been called "molecular sieves" and are used in various ways to make full use of these properties.
[0005] There are more than 250 known zeolite framework structures currently approved by the International Zeolite Association. It is necessary to have a new structure with a property different from the property of known materials for improving the performance of many organic compound conversions and adsorption processes. Each structure has a unique hole, channel and cage size, which produces its specific properties as described above. Each framework structure also has a specific composition. It is always important to prepare improvements in purer single-phase materials. About the catalysis in organic compound conversion reactions, it is valuable to provide a molecular sieve with an increased acid site. SUMMARY OF THE INVENTION
[0007] According to the present disclosure, 1,3-bis(1-adamantyl)imidazole is used. A new crystalline aluminogermanosilicate molecular sieve denoted SSZ-121 with increased acid sites and a unique composition was synthesized using cations as structure directing agents. The synthesis was carried out via a boron route.
[0008] The SSZ-121 molecular sieve of the present application contains some boron in its framework. In one embodiment, the amount of boron may range from 50 to 250 ppm.
[0009] The aluminogermanosilicate SSZ-121 molecular sieve of the present application having increased acid sites and thus enhanced acidity may have a chemical composition comprising the following molar relationship:
[0010] Table 1
[0011] Widest secondary <![CDATA[(SiO2+GeO2) / Al2O3]]> ≥30 ≥50
[0012] The prepared SSZ-121 zeolite also has increased acid sites and some boron in the framework.
[0013] In one embodiment, a method for synthesizing the SSZ-121 aluminum germanosilicate molecular sieve of the present application is provided, the method comprising (1) providing a reaction mixture comprising: (a) a FAU framework type zeolite; (b) a germanium source; (c) a boron source; (d) a 1,3-bis(1-adamantyl)imidazole cationic structure directing agent (Q); (e) fluoride ion source; and (f) water; (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of borogermanosilicate molecular sieve; (3) removing the structure directing agent (Q); and (4) treating the remaining crystals to replace boron in the framework with aluminum.
[0014] Thus, the boron route includes preparing a germanosilicate molecular sieve comprising boron in the framework. The boron molecular sieve has a powder X-ray diffraction pattern in its as-synthesized form including at least the following 2θ scattering angles: 6.3±0.2; 7.0±0.2; 9.5±0.2; 13.0±0.2; 16.0±0.2; 18.5±0.2; 19.8±0.2; 21.2±0.2; 24.0±0.2; 25.0±0.2; 26.5±0.2; 28.5±0.2; and 30.0±0.2 degrees 2θ.
[0015] This borogermanosilicate molecular sieve is then treated to replace the boron in the framework with aluminum, thus resulting in increased acid sites.
[0016] In another embodiment, a method of converting a feedstock comprising an organic compound to a conversion product is provided, comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising an aluminogermanosilicate molecular sieve described herein in active form.
[0017] Among other factors, the method of the present application allows technicians to obtain SSZ-121 molecular sieves with increased acid sites, that is, SSZ-121 is rich in acid or has enhanced acidity. The increased acid sites mean that the method of the present application is used with the boron path of the molecular sieve, and the SSZ-121 molecular sieve can be obtained with more acid sites than the conventional molecular sieve prepared by direct method (with aluminum sites and no boron). When using conventional approaches, it is found that some amorphous phases appear, so the loss of Al acid sites has been experienced. It is quite surprising to find that by first inserting boron into the framework, and then replacing boron with aluminum, a molecular sieve with a relatively increased amount of acid sites can be achieved. Therefore, SSZ-121 is rich in acid or has enhanced acidity. The increased acid sites can lead to improved catalytic properties for the SSZ-121 molecular sieve of the present application. The SSZ-121 molecular sieve of the present application also contains a minimum amount of boron.
[0018] Details
[0019] definition
[0020] The term "framework type" has the meaning described in "Atlas of Zeolite Framework Typess" by Ch. Baer locher, LB McCusker and DH Olsen (Elsevier, 6th revised edition, 2007).
[0021] The term "zeolite" refers to a synthetic aluminosilicate molecular sieve having a framework built of alumina and silica (ie, repeating AlO4 and SiO4 tetrahedral units).
[0022] The term "aluminogermanosilicate" refers to a molecular sieve having a framework constructed of AlO4, GeO4 and SiO4 tetrahedral units. Aluminogermanosilicate may contain only the specified oxides, in which case it may be described as a "pure aluminogermanosilicate" or it may also contain other oxides.
[0023] The term "as-synthesized" is used herein to refer to the molecular sieve in its form after crystallization and before removal of the structure directing agent.
[0024] The term "anhydrous" is used herein to refer to molecular sieves that are substantially free of physically and chemically adsorbed water.
[0025] "Increased" or "more" acid sites means that the SSZ-121 molecular sieve prepared by the method of the present application contains more acid sites than those obtained by conventionally preparing molecular sieves without the boron path of the present application. When the conventional direct method using aluminum is adopted, an amorphous phase causing the loss of Al acid sites is found to occur. It is quite surprising to find that by first inserting boron into the SSZ-121 framework, and then replacing boron with aluminum, a SSZ-121 molecular sieve with more aluminum acid sites, i.e., a relatively large amount of acid sites, can be obtained, which is more than what will be obtained in the initial preparation of the molecular sieve if boron is not introduced. Therefore, SSZ-121 is rich in acid or has enhanced acidity. This increased acidity can affect and improve the catalytic properties of the molecular sieve. The molecular sieve will be quite useful in, for example, converting a raw material containing an organic compound into a conversion product. Due to the boron path, some boron is indeed retained in the SSZ-121 molecular sieve.
[0026] Synthesis of molecular sieves
[0027] The molecular sieve SSZ-121 of the present application can be synthesized by the boron route by a method comprising the following: (1) preparing a reaction mixture comprising: (a) a FAU framework type zeolite; (b) a germanium source; (c) a boron source; (d) a 1,3-bis(1-adamantyl)imidazole A cationic structure directing agent (Q); (e) a fluoride ion source; and (f) water; (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of boron SSZ-121 molecular sieve. The boron-containing SSZ-121 molecular sieve is then treated to remove SDA and then treated to replace some or all of the boron with aluminum. The result is SSZ-121 with increased acid sites.
[0028] The reaction mixture may have a composition in terms of molar ratios within the ranges listed in Table 2:
[0029] Table 2
[0030] Reactants Widest secondary <![CDATA[(SiO2+GeO2) / B2O3]]> ≥10 ≥15 <![CDATA[Q / (SiO2+GeO2)]]> 0.10 to 1.00 0.20 to 0.70 <![CDATA[F / (SiO2+GeO2)]]> 0.10 to 1.00 0.20 to 0.70 <![CDATA[H2O / (SiO2+GeO2)]]> 2 to 10 4 to 8 <![CDATA[SiO2 / GeO2]]> 4 to 12 6 to 10
[0031] wherein Q comprises 1,3-bis(1-adamantyl)imidazole cation.
[0032] Suitable silicon oxide sources can include any suitable known sources such as colloidal silicon dioxide, fumed silica, precipitated silica or alkali metal silicate. FAU framework type zeolite such as zeolite Y can also be a silicon oxide source. In such a case, the FAU framework type zeolite has at least 250 and preferably at least 300 (e.g., 300 to 500) very high SiO2 / Al2O3 mol ratio. The FAU framework type zeolite can include two or more FAU framework type zeolites with different SiO2 / Al2O3 mol ratios. The FAU framework type zeolite can be zeolite Y, or any of its various post-synthesis modified forms, as known in the art.
[0033] Suitable sources of germanium include germanium oxide and germanium alkoxides (eg, germanium ethoxide, germanium isopropoxide).
[0034] Silicon and germanium may be present in the reaction mixture in a SiO2 / GeO2 molar ratio of 4-12 (eg, 6 to 10).
[0035] Suitable sources of boron may include boric acid (which is preferred).
[0036] Suitable sources of fluoride ions include hydrogen fluoride, ammonium fluoride and ammonium bifluoride.
[0037] The structure directing agent comprises 1,3-bis(1-adamantyl)imidazole represented by the following structure (1): Cation (Q):
[0038]
[0039] Suitable sources of Q are hydroxides, chlorides, bromides and / or other salts of quaternary ammonium compounds and mixtures thereof.
[0040] The reaction mixture can have a Q / F molar ratio in the range of 0.80-1.20 (eg, 0.85 to 1.15, 0.90 to 1.10, 0.95 to 1.05, or 1 to 1).
[0041] The reaction mixture may contain seeds of a molecular sieve material, such as boron SSZ-121 from a previous synthesis, in an amount of 0.01-10,000 ppm by weight (e.g., 100-5000 ppm by weight) of the reaction mixture. Seeding may be advantageous in reducing the amount of time required for complete crystallization to occur. Additionally, seeding may result in a product that is higher in purity by promoting nucleation and / or formation of boron SSZ-121 over any unwanted phases.
[0042] Note that the reaction mixture components can be supplied by more than one source. In addition, two or more reaction components can be provided by one source. The reaction mixture can be prepared in batches or continuously.
[0043] The reaction mixture may be prepared batchwise or continuously.The crystal size, morphology and crystallization time of the molecular sieves described herein may vary depending on the nature of the reaction mixture and the crystallization conditions.
[0044] Crystallization and post-synthesis processing
[0045] In accordance with the boron route, the crystallization of the boron SSZ-121 molecular sieve from the above reaction mixture can be carried out at a temperature of 100° C. to 200° C. (e.g., 150° C. to 175° C.) in a suitable reactor vessel (e.g., a polypropylene tank or a Teflon-lined or stainless steel autoclave) under static, tumbling or stirring conditions for a time sufficient for crystallization to occur at the temperature used (e.g., 1 day to 14 days, or 2 days to 10 days). The hydrothermal crystallization process is typically carried out under pressure, such as in an autoclave, and is preferably carried out under autogenous pressure.
[0046] Once the boron molecular sieve crystals are formed, the solid product can be recovered from the reaction mixture by standard mechanical separation techniques such as centrifugation or filtration. The recovered crystals are washed with water and then dried to obtain the boron SSZ-121 molecular sieve crystals as synthesized. The drying step can be carried out at an elevated temperature (e.g., 75° C. to 150° C.) for several hours (e.g., about 4 to 24 hours). The drying step can be carried out under vacuum or at atmospheric pressure.
[0047] As a result of the crystallization process, the recovered crystalline molecular sieve product contains within its pore structure at least a portion of the structure directing agent used in the synthesis.
[0048] The as-synthesized molecular sieve may also be subjected to treatment to remove part or all of the structure directing agent used in its synthesis. This is conveniently achieved by heat treatment (i.e., calcination), wherein the as-synthesized material is heated at a temperature of at least about 370°C for at least 1 minute and generally not longer than 20 hours. Although subatmospheric pressure can be used for heat treatment, atmospheric pressure is desired for convenience reasons. Heat treatment may be performed at a temperature of up to about 925°C. Heat treatment may be performed in an atmosphere selected from air, nitrogen, or a mixture thereof. For example, heat treatment may be performed in air at a temperature of 400°C-600°C for a period of 3-8 hours. Alternatively, the structure directing agent Q may be removed by treatment with ozone. Ozone treatment may include heating the as-synthesized molecular sieve in the presence of ozone, such heating may be at a temperature of 50°C-350°C (e.g., 100°C-300°C, or 125°C-250°C). In one embodiment, treatment with ozone is preferred because it can provide a higher micropore volume.
[0049] The molecular sieve crystals may then be treated to replace at least some of the boron with aluminum, although preferably most (90%) of the boron, if not all. In one embodiment, the amount of boron remaining after the exchange may be an amount ranging from 50 to 250 ppm. Conventional techniques may be used, such as by ion exchange. However, treating the molecular sieve with an aqueous solution of aluminum nitrate is a preferred way to replace the boron in the framework with aluminum. The treatment may be accomplished by contacting the molecular sieve with an aluminum nitrate solution under reflux.
[0050] Characterization of Molecular Sieve
[0051] The acid enhanced molecular sieve SSZ-121 (also containing some residual boron) may have a chemical composition comprising the following molar relationships listed in Table 1:
[0052] Table 1
[0053] Widest secondary <![CDATA[(SiO2+GeO2) / Al2O3]]> ≥30 ≥50
[0054] In some aspects, the molecular sieve can have a SiO2 / GeO2 molar ratio in the range of 4-12 (eg, 6-10).
[0055] In another aspect, the molecular sieve boron SSZ-113 having an increased number of acid sites may have a chemical composition comprising the following molar relationship:
[0056] Al2O3:(n)(SiO2+GeO2)
[0057] wherein n is ≥30 (eg, 30 to 500, 30 to 250, 30 to 150, ≥50, 50 to 250, or 50 to 150).
[0058] The acid enhanced molecular sieve SSZ-121 exhibits a powder XRD pattern having at least the following 2θ scattering angles: 6.5±0.2, 9.5±0.2, 13.0±0.2, 18.5±0.2, 19.8±0.2, 21.2±0.2, 24.0±0.2, 25.0±0.2, 26.5±0.2, 28.5±0.2 and 30.0±0.2 degrees 2θ.
[0059] The powder X-ray diffraction patterns presented herein can be collected by standard techniques. The radiation is CuKα radiation. The peak heights and positions vary with 2θ (where θ is the Bragg angle), the relative intensities of the peaks are read (adjusted for background), and d (corresponding to the interplanar spacing of the recorded lines) can be calculated.
[0060] The slight changes in the diffraction pattern can be caused by the changes in the molar ratio of the framework material of the sample caused by the change in the lattice constant. In addition, disordered materials and / or sufficiently small crystals will affect the shape and intensity of the peak, thereby causing significant peak broadening. The slight changes in the diffraction pattern can also be caused by the changes in the organic compounds used in the preparation. Calcination can also cause slight shifts in the XRD pattern. Despite these slight disturbances, the basic lattice structure remains unchanged.
[0061] Industrial Applicability
[0062] Acid site enhanced molecular sieve SSZ-121 (wherein some or all of the structure directing agent is removed) can be used as an adsorbent or as a catalyst to catalyze a wide variety of organic compound conversion processes, including many processes that are currently of commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by acid-rich SSZ-121 (either by itself or in combination with one or more other catalytically active substances including other crystalline catalysts) include those that require the catalyst to have acid activity and catalytic metals. Examples of organic conversion processes that can be catalyzed by the SSZ-121 of the present application with increased acid sites include aromatization, cracking, hydrocracking, disproportionation, alkylation, oligomerization and isomerization.
[0063] As in the case of many catalysts, it is desirable to combine SSZ-121 rich in acid sites with another material that is resistant to the temperature and other conditions used in the organic conversion process. Such materials include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clays, silica and / or metal oxides such as alumina. The latter may be naturally occurring or in the form of a gelatinous precipitate or gel, including a mixture of silica and metal oxides. The use of materials (i.e., in combination with active SSZ-121 rich in acid or present in the synthesis process of new materials) tends to change the conversion and / or selectivity of the catalyst in some organic conversion processes. Inactive materials are suitable for playing the role of diluents to control the amount of conversion in a given method, so that products can be obtained in an economical and orderly manner without adopting other means of controlling the reaction rate. These materials can be incorporated into naturally occurring clays (e.g., bentonite and kaolin) to improve the crushing strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) serve as binders for catalysts. It is desirable to provide a catalyst with good crushing strength because it is desirable to prevent the catalyst from breaking into powdered materials in commercial use. These clay and / or oxide binders are normally used only for the purpose of improving the crush strength of the catalyst.
[0064] Naturally occurring clays that can be compounded with the acid site rich SSZ-121 of the present application include montmorillonite and the kaolin family, which includes sub-bentonite and kaolins commonly known as Dixie, McNamee, Georgia and Florida clays or other kaolins in which the major mineral components are halloysite, kaolinite, dickite, nacrite or anthracite. Such clays can be used in their original state as originally mined or initially subjected to calcination, acid treatment or chemical modification. Binders that can be used to compound with the acid rich SSZ-121 also include inorganic oxides such as silicon dioxide, zirconium oxide, titanium oxide, magnesium oxide, beryllium oxide, aluminum oxide and mixtures thereof.
[0065] In addition to the aforementioned materials, the acid-rich SSZ-121 of the present application can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0066] The relative proportions of the acid site rich SSZ-121 and the inorganic oxide matrix can vary widely, with the SSZ-121 content ranging from 1-90 wt % (eg, 2 to 80 wt %) of the composite. Example
[0067] The following illustrative examples are intended to be non-limiting.
[0068] Example 1
[0069] Synthesis of SSZ-121 Boron
[0070] To the tared cup was added 42.5 grams of SDA solution as OH, which was 0.28 mole. Then to the solution were added (a) 1.20 grams of Tosoh HUA 390FAU zeolite with SAR=500, (b) 0.225 grams of germanium dioxide (c) 0.06 grams of boric acid. The open tared cup was then placed in a hood for evaporation until the H2O / TO2 ratio dropped to 7. The reaction then provided HF in an amount equal to the amount of SDA in millimoles. The contents of the cup were then transferred to a 23 ml Teflon cup for a Parr stainless steel reactor, which was closed and loaded onto a rotating spit (43 RPM) in a convection oven. Crystallization was carried out at 160° C. over about 15 days. (It may be advantageous to use typically about 3% by weight of the Tosoh reagent used to seed the zeolite synthesis). The product was collected and washed 4 times with 50 ml H2O in each aliquot.
[0071] The recovered product can then be treated to remove SDA before being treated with aluminum nitrate at reflux to provide SSZ-121 with increased acid sites.
[0072] Example 2
[0073] Calcination of SSZ-121 Boron
[0074] The as-synthesized boron molecular sieve of Example 1 can be calcined inside a hearth furnace under air flow by heating to 550°C at a rate of 1°C / min and holding at 550°C for 5 hours, cooled and then analyzed by powder XRD.
[0075] Analysis of the calcined product by the t-curve method of nitrogen physical adsorption will show that the sample has at least 0.144 cm 3 / g of micropore volume.
[0076] Example 3
[0077] Although one can calcine boron SSZ-121, it is preferred to first treat the zeolite with ozone at 150°C to remove the SDA guest molecules. In addition, it has been found that much SDA can be first removed by treatment with dimethylformamide in a closed reactor at 150°C; 1 gram of the as-prepared zeolite and 7 ml of dimethylformamide, static heating for 3-5 days.
[0078] The B SSZ-121 as prepared can then be charged to the tank and ozone passed through the tank while heating to 150°C. The treatment can be carried out for 16-20 hours. The mass loss (if not treated with dimethylformamide) is about 40%.
[0079] The XRD pattern will be essentially the same as previously described.
[0080] Example 4
[0081] The porous B SSZ-121 from Example 3 can then be treated with a 0.2 molar aluminum nitrate solution (10 grams of solution per gram of zeolite) by heating to 95°C in a closed system for 5 days. The pH of the treatment solution will drop from about 2.5 to 1.55, which is consistent with the Al cations having been removed from solution and placed in the zeolite. The recovered solids can be filtered and then washed with 25cc of 0.01 normal HCl before any water washes. The acid wash first is to keep any aluminum cations in solution through the washing steps so that the Al is not deposited on the solids.
[0082] Example 5
[0083] Bronsted acidity
[0084] The Bronsted acidity of the molecular sieve of Example 4 can be determined by n-propylamine temperature programmed adsorption (TPD) adapted from the public descriptions of TJ Gricus Kofke et al. (J. Catal. 1988, 114, 34-45), TJ Gricus Kofke et al. (J. Catal. 1989, 115, 265-272) and JG Tittensor et al. (J. Catal. 1992, 138, 714-720). The sample can be pretreated at 400° C.-500° C. in flowing dry H2 for 1 hour. The dehydrated sample is then cooled down to 120° C. in flowing dry helium and maintained at 120° C. for 30 minutes in flowing helium saturated with n-propylamine for adsorption. The sample saturated with n-propylamine is then heated in flowing dry helium at a rate of 10° C. / min up to 500° C. The Bronsted acidity was calculated based on the weight loss versus temperature by thermogravimetric analysis (TGA) and the effluent NH3 and propylene by mass spectrometry.
[0085] The desorption data for the peak near 400°C can be converted to a measured acidity of 160 micromol / g. This is sufficient to have Bronsted acid sites for catalysis.
[0086] As used in this disclosure, the words "comprising" or "comprising" are intended to be open ended transitional, meaning the specified elements are included but not necessarily excluding other unspecified elements. The phrases "consisting essentially of" or "consisting essentially of" are intended to mean excluding other elements of any significance to the composition. The phrases "consisting of" or "consisting of" are intended to be transitional, meaning excluding all but the recited elements except for only minor trace impurities.
[0087] All patents and disclosures cited herein are incorporated herein by reference to the extent that they are not inconsistent with this article. It will be understood that some of the above-mentioned structures, functions and operations of the above-mentioned embodiments are not necessary for implementing the present invention, and are included in the description only for the completeness of one or more exemplary embodiments. In addition, it will be understood that the specific structures, functions and operations set forth in the above-mentioned patents and disclosures can be implemented in conjunction with the present invention, but they are not necessary for the implementation of the present invention. It should therefore be understood that the present invention can be implemented in a manner different from the specific description without actually departing from the spirit and scope of the present invention as defined by the appended claims.
Claims
1. An SSZ-121 molecular sieve having increased acid sites and a powder X-ray diffraction pattern having at least the following 2θ scattering angles: 6.5±0.2, 9.5±0.2, 13.0±0.2, 18.5±0.2, 19.8±0.2, 21.2±0.2, 24.0±0.2, 25.0±0.2, 26.5±0.2, 28.5±0.2, and 30.0±0.2 degrees 2θ, wherein the molecular sieve further comprises boron in its framework.
2. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: Al2O3:(n)(SiO2+GeO2) Where n is ≥30.
3. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: Al2O3:(n)(SiO2+GeO2) Where n is ≥50.
4. The molecular sieve according to claim 1, having a chemical composition comprising the following molar relationship: (SiO2+GeO2) / Al2O3≥30.
5. The molecular sieve according to claim 1, having a chemical composition comprising the following molar relationship: (SiO2+GeO2) / Al2O3≥50.
6. A method for synthesizing the molecular sieve according to claim 1, the method comprising: (1) preparing a reaction mixture comprising: (a) a FAU framework-type zeolite having a SiO2 / Al2O3 molar ratio of at least 300; (b) Source of germanium; (c) boron source; (d) containing 1,3-bis(1-adamantyl)imidazole Cationic structure directing agent (Q); (e) a fluoride ion source; and (f) water; (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of a boron-containing molecular sieve; (3) removing the structure directing agent (Q); and (4) Replacing some of the boron in the crystals of the molecular sieve with aluminum.
7. The method according to claim 6, wherein the reaction mixture has the following composition in terms of molar ratio:
8. The method according to claim 6, wherein the reaction mixture has the following composition in terms of molar ratio:
9. The method of claim 6, wherein the FAU framework-type zeolite is zeolite Y.
10. The method of claim 6, wherein the crystallization conditions include a temperature of 100°C to 200°C.
11. The process of claim 6, wherein the reaction mixture has a Q / F molar ratio in the range of 0.8-1.
2.
12. The method according to claim 6, wherein Q is removed by calcination.
13. The method of claim 6, wherein Q is removed by treatment with ozone.
14. The method of claim 6, wherein replacing boron with aluminum comprises refluxing the molecular sieve crystals with a solution of aluminum nitrate.
15. A method of converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 1 under organic compound conversion conditions.
16. Product prepared by the process according to claim 6.
17. Product prepared by the process according to claim 14.
